Statistical Analysis of Stone Mastic Asphalt Incorporating Kenaf Fibre - G., Danoshini; A., Baqadeem; A. K. S., Al-Shakhrit; N. E., Jasni; Khairil Azman, Masri (Penerbit UMP, 2021)
Stone mastic asphalt consists of two components of coarse aggregate and bitumen-filled mortar (bituminous blend, filler, and stabilizing additives like cellulosic or mineral fibers). Such a form of hot mix asphalt (SMA) was first developed in Germany in the mid-1960s to cope with corrosion and ribbed wheel destruction. The mixture was then known as stone mastic asphalt, which was not only immune to ribbed wheels but also has strong resistance against rutting. One of the most significant problems when constructing the stone mastic asphalt pavement is permanent deformation. By a load of traffic and the strain of the tires, much of the irreversible deformation happens in the ground. According to a previous study, researchers have stated that the kenaf fiber's physical strength and thermal characteristics are superior compared to other forms of natural fiber polymer composites, and therefore deemed a desirable applicant for elevated-performance natural fiber composite materials. Thus, the aim of this study is to assess the mechanical performance of stone mastic asphalt incorporating kenaf fiber by developing a regression model. A set of data of SMA mixture incorporating various percentages of kenaf fiber were assessed through statistical analysis in Minitab 19 by using the resilient modulus as the dependant variable in the first model and the accumulated strain from the dynamic creep test as the dependant variable in the second model. The regression models showed a positive impact of kenaf fiber as an additive in the SMA mixture. For more future studies, it is recommended to analyze the effect of the various proportions of kenaf fiber with bitumen modification towards stone mastic asphalt performance that will render the satisfactory performance of SMA during service.